Digital Archive Information Systems Streamline School Administration Amidst Resource Limitations: Sistem Informasi Arsip Digital Merampingkan Administrasi Sekolah Di Tengah Keterbatasan Sumber Daya - Laksono Reni Allysa Putri F; Lailul Mursyidah; Irmayanti Dwi Saputri; Salma Eka Atminingsih; Anafi Dewi Anggraini; Laila Ihza Masithah (Proceedings of The ICECRS, 2025)
General Background Information and communication technology advancements necessitate modern digital archiving solutions to resolve conventional records management challenges. Specific Background Indonesian educational institutions are transitioning toward digital frameworks, yet schools frequently encounter operational barriers such as limited specialized personnel and unstable internet connectivity. Knowledge Gap Although theoretical models suggest digitalization guarantees administrative efficiency, practical implementation frequently stalls due to inadequate infrastructure and personnel capability shortages. Aims This study analyzes the adoption of a Dynamic Archiving Information System at a public secondary school to evaluate its operational outcomes. Results Findings reveal that the digital platform significantly accelerates document accessibility, fortifies data security, and reduces operational costs; however, dual-role teaching staff and unstable network connections severely disrupt optimal utilization. Novelty This research distinctly isolates the operational friction caused by assigning complex digital archiving responsibilities to non-specialized teaching personnel within resource-constrained educational environments. Implications Sustaining digital administrative transitions requires immediate strategic investments in specialized technical staff, robust network infrastructure, and clear digital records management protocols. Highlights: Automated record platforms accelerate document retrieval and fortify institutional data confidentiality. Dual-role teaching personnel struggle to manage specialized database tasks efficiently. Unstable network connectivity directly disrupts the transition from manual to electronic documentation. Keywords: Dynamic Archiving, Information Technology, Educational Management, Digital Transformation, Data Security